I like fruit - Goldman, Ethel (Lerner Publications Company Minneapolis, 1971)
Briefly discusses characteristics of fruit as opposed to vegetables; then describes twelve specific fruits, their uses throughout history, how they are eaten, and how they grow.
7 - 9 years
Keywords: Fruit